The effect of training GPs in motivational interviewing on incident cardiovascular disease and mortality in people with screen- detected diabetes. Results from the ADDITION- Denmark randomised trial. Issue 1 (April 2020) - Charles, Morten; Bruun, Niels Henrik; Simmons, Rebecca; Dalsgaard, Else-Marie; Witte, Daniel; Jorgensen, Marit; Christensen, Bo; Maindal, Helle Terkildsen; Rubak, Sune; Sandbaek, Annelli; Lauritzen, Torsten
No abstract available